Framework for adoption of customer relationship management systems in hospital - Ibrahim, Huda; Mohd, Haslina; Mohd Noor, Nor Azila; Rababah, Khalid Ali (Universiti Utara Malaysia, 2012)
Customer Relationship Management (CRM) systems enable hospitals to provide better quality of services, to improve customers’ satisfaction, and to increase their profitability and competitiveness.However, there is little attention and lack of adoption of the CRM systems in private hospitals in Malaysia. Moreover, few studies have investigated the factors influencing the adoption of the CRM systems in private hospitals in Malaysia.The main objective of this study is therefore to construct an adoption model of CRM systems in the healthcare industry.Self administered questionnaires were used to collect the data from the top management employees in private hospitals in Malaysia.A total of 148 questionnaires distributed in which 79 questionnaires (53%) were returned.The data of 72 valid questionnaires were analysed using Correlation and Multiple Regression techniques to validate the model.The model, adapted from the Diffusion of Innovation (DOI) theory and the Model of Information System (IS) Innovation, was built to relate innovation, organizational, and environmental factors to the perception of the CRM system’s benefits and implementation plans.Findings indicate that innovation, organizational, and environmental factors have positive significant relationships (p >0.05).The results of the study such as the constructed model, provide a set of adoption guidelines that contributes to a successful adoption and implementation of the CRM systems.The model also contributes to the body of knowledge in the DOI theory, the Model of IS Innovation, and the CRM domain. In practical, the results have many implications such as emphasizing on the roles of the CRM systems on solving major problems in hospitals and encouraging the vendors of the CRM systems to improve their marketing strategies and to provide the CRM systems at reasonable prices.